Transferrin levels are associated with malnutrition markers in hemodialysis patients in KwaZulu-Natal, South Africa - Sherilene Benjamin; Alain Assounga (Renal Failure)
Introduction Malnutrition is a global phenomenon and may be contributing to the increasing size of the hemodialysis (HD) population in South Africa and is affecting morbidity and clinical outcomes. Our study assessed whether transferrin could be a possible marker for malnutrition in the HD population.Methods Clinical parameters (including skinfold thickness and mid-upper arm circumference [MUAC]) and laboratory markers (including transferrin and hemoglobin) were measured during a six-month period in a sample of 59 HD patients.Results Linear regression analysis showed that MUAC (p = 0.027) as well as skinfold thickness (p = 0.021) had a significant association with transferrin levels within the HD participants. There was no significant association between transferrin levels or MUAC with hemoglobin levels (p = 0.075). Furthermore, the study found that decreased transferrin levels (< 2.15 g/dL to 3.80 g/dL) were closely related to malnutrition in the malnutrition distribution groups within the study, with 97.7% of HD participants being classified in one of the malnutrition groups.Conclusion Thus, transferrin levels are a valuable marker for malnutrition within the HD patient population and can be included along with clinical assessment parameters such as MUAC and skinfold thickness as primary indicators for malnutrition.